The Effect of Green Accounting on Financial Resilience in Facing Climate Change Risks - Ridayati, Salija; Setyowati, Rulis; Pandin, Maria Yovita R. (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the financial resilience of banking companies in facing climate change risks through the implementation of green accounting in the 2022-2023 period. The increasing risk of climate change affects the financial sector, including banking, which needs to adapt to maintain financial stability. Green accounting as an accounting approach that considers environmental aspects in financial reporting is expected to be a solution to increase corporate resilience in facing climate change risks. This study uses quantitative methods and secondary data analysis from the annual reports of banking companies that have implemented green accounting. The study population includes 46 banking companies listed on the IDX for the 2022–2023 period. The sample was selected using purposive sampling, consisting of Bank BCA, Bank BRI, and Bank BNI, based on certain criteria. The results of the study show that the implementation of green accounting contributes positively to corporate financial resilience, especially in terms of climate risk mitigation and improving corporate reputation. This study contributes to providing empirical evidence on the effectiveness of green accounting as a strategic tool in corporate financial planning, which supports banks in responding to climate change challenges more effectively in the future.